Genetic variants in Transient Receptor Potential cation channel, subfamily M 1 (TRPM1) and their risk of albuminuria-related traits in Mexican Americans - Thameem, Farook (2011)
BACKGROUND: Evidence for linkage of albuminuria to GABRB3 marker region on chromosome 15q12 was previously reported in Mexican Americans. The objective of this study is to scan a positional candidate gene, Transient Receptor Potential cation channel, subfamily M 1 (TRPM1), for genetic variants that may contribute to the variation in albumin-to-creatinine ratio (ACR). METHODS: To identify the sequence variants, the exons and 2 kb putative promoter region of TRPM1 were PCR amplified and sequenced in 32 selected individuals. Identified variants were genotyped in the entire data set (N=670; 39 large families) by TaqMan assays. Association analyses between the sequence variants and ACR, type 2 diabetes (T2DM) and related phenotypes were carried out using a measured genotype approach as implemented in the program SOLAR. RESULTS: Sequencing analysis identified 18 single nucleotide polymorphisms (SNPs) including 8 SNPs in the coding regions, 7 SNPs in the promoter region and 3 SNPs in introns. Of the 8 SNPs identified in the coding regions, 3 were non synonymous [Met(1)Thr, Ser(32)Asn, Val(1395)Ile] and one SNP caused stop codon (Glu1375/*). Of the SNPs examined, none of them exhibited statistically significant association with ACR after accounting for the effect of age, sex, diabetes, duration of diabetes, systolic blood pressure and anti-hypertensive medications. However, a SNP (rs11070811) located in the putative promoter region showed a modest association with triglycerides levels (P = 0.039). CONCLUSION: The present investigation found no evidence for an association between sequence variation at the TRPM1 gene and ACR in Mexican Americans, although it appears to have modest influence on T2DM risk factors.